Trends and factors for dropout among secondary school students in Perak - Mokshein Siti Eshah, Kung Teck Wong, Ibrahim Haniz (Universiti Pendidikan Sultan Idris, 2016)
Trends and factors for dropout among secondary school students in Perak by Mokshein Siti Eshah, Kung Teck Wong, Ibrahim Haniz,